Sistem Pendukung Keputusan Pemilihan Mobil Bekas Berbasis Web Menggunakan Metode Weighted Product - Nandang Prayogi; Pantjawati Sudarmaningtyas; Achmad Arrosyidi (Indonesian Society of Applied Science, 2025)
Limited information about vehicle conditions and manual selection methods often leaves prospective used car buyers uncertain. This problem occurs at the Sumber Rejeki Showroom, which has not yet adopted a decision support system to assist buyers in selecting used cars. This study aims to develop a web-based decision support system for used car selection using the Weighted Product (WP) method. Using a quantitative approach, the study involves collecting car attribute data, assigning criterion weights, and testing the system. Validation is conducted by comparing system-generated rankings with manual WP calculations and by performing white box testing to verify the correctness of the system logic. The system development follows the intelligence, design, choice, and implementation stages. The results show that the system’s ranking aligns exactly with manual calculations, confirming the proper application of the WP method. White box testing indicates error-free WP computations, and a Cyclomatic Complexity score of 10 suggests that the code is maintainable. Overall, the study demonstrates that the developed web-based decision support system can effectively support used car selection, enhance decision-making efficiency, and increase user confidence.